Peran Majelis Kehormatan Mahkamah Konstitusi Dalam Penegakan Undang Undang Dasar Dan Penyelesaian Pelanggaran Kode Etik Ketua Mahkamah Konstitusi - Alaya Rihadatul Aisya; Amelia Intan Safitri; Astri Nuraina; Najwa Yustitia Aequo; Tasya Halimah Nia Purwanti; Kuswan Hadji (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The Ministry of Constitution have a vision on enforcing the Constitution in order to actualize the country of democracy, as well as the ambitions of our state law that is; to create a dignified life of the people and the nation. The purpose of the said vision is so that it can serve as a guideline, to exercise responsible judicial power in accordance with the mandate of the constitution, and independently for the Constitutional Court. The role of the Honorary Council of the Constitutional Court is to maintain and supervise the behavior of the Constitutional Court using descriptive research methods that are quantitative or non-quantitative. directly by conducting a literature review taken from search and normative results. The Honorary Council of the Constitutional Court is an institution that plays a role in monitoring and examining the actions of judges in the constitutional court which are suspected of violating the constitution. The authority of the Honorary Council according is to examine and make decisions on reports and information that the respondent judge is suspected of committing serious violations. The decision of the Honorary Council of the Constitutional Court as a means of enforcing the code, ethics and behavior of Constitutional judges is final and binding. Role of the Law The Constitution by the Constitutional Court regarding Cases of Violations of the Code of Ethics is the legal basis and source of law for making rules as code and ethical guidelines in carrying out the judicial duties of the Constitutional Court, Honorary Council. The Constitutional Court is the body responsible for guaranteeing and implementing the basic principles of the